Doctrine Of 'Eschatology' - Lilisantika; Akelince Doo (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The Doctrine of the End Times or Eschatology is a significant part of Christian theology that focuses on the fate of humanity and the events that will occur in the future. This doctrine explores the resurrection of the dead, the understanding of eschatology, the concept of the end times, the second coming of Christ, and the importance of understanding eschatology in preparing for the future.